EFFECT OF FIELDTRIP STRATEGY ON ACADEMIC ACHIEVEMENT OF SENIOR SECONDARY SCHOOL BIOLOGY STUDENTS IN EKITI LOCAL GOVERNMENT AREA OF KWARA STATE, NIGERIA - Akanbi, Adejoke Arinlade; Adewumi, Gabriel Segun; Muraina, Kamilu Olanrewaju (JSE, 2024)
This study determined the effect of field trip strategy on academic achievement of students’ in Biology. The study adopted the pretest-posttest control group, quasi-experimental design. 80 SSII Biology students from two (2) co-educational schools in Ekiti Local Government Areas of Kwara State were randomly assigned to treatment group. The instrument used was Biology Student Achievement Test (r=0.86) and Teachers Instructional guides on Fieldtrip strategy. Two Research Questions and hypotheses guided the study. Descriptive statistics of means and standard deviation were used to answer the research questions and inferential statistics of Analysis of Covariance was used to test the hypotheses at 0.05 level of significance. The results of the study showed that fieldtrip strategy enhanced students’ performance in biology than conventional method. There is a significant difference between the achievements mean score of the students exposed to fieldtrip strategy in biology and compare with their counterpart taught using conventional strategy. There was no significant difference between the mean achievement scores of male and female students exposed to fieldtrip strategy in biology and compare with their counterpart taught using conventional strategy. Based on the findings, biology teachers should adopt fieldtrip strategy to teach the students, so that they learn better as it could foster confidence in the students and improve their achievement.